Autologous stem cell transplantation for mantle cell lymphoma – single centre experience - Szcześniak, Magdalena; Armatys, Anna; Kurzawa, Rafał; Kandzia, Tomasz; Kozioł, Dominika; Frankiewicz, Andrzej; Kopińska, Anna; Krawczyk-Kuliś, Małgorzata; Kyrcz-Krzemień, Sławomira; Helbig, Grzegorz (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Mantle cell lymphoma (MCL) is a B-cell neoplasm showing resistance to conventional chemotherapy. High-dose chemotherapy followed by autologous stem cell transplantation (ASCT) may result in higher progression-free (PFS) and overall survival (OS) when used as a consolidation for younger and fit patients. Material and methods: We retrospectively evaluated the results of ASCT for MCL. Patients were transplanted after achieving first or subsequent complete or partial response after conventional chemotherapy. Results: Twenty patients (7 male and 13 female) at median age of 59 years (range 41–68) were included. 90% of transplanted patients had stage III/IV disease at diagnosis and low, intermediate and high MIPI scores occurred in 5, 9 and 6 patients respectively. Induction chemotherapy consisted of the R-CHOP regimen in all patients except one who received R-CVAD. The disease status at transplant was as follows: first complete response (n = 13); second complete response (n = 4) and partial response (n = 3). The conditioning regimen prior to ASCT consisted of CBV and BEAM for 18 and 2 patients, respectively. The transplant-related mortality was 0% at day 100. Median OS and PFS were 48 and 29.8 months, respectively. The estimated 5-year OS and PFS were found to be 52% and 35%, respectively. After median follow-up after ASCT of 36 months (range 11–73), 10 patients were alive with 8 remaining in complete remission (CR) whereas 2 relapsed and received salvage chemotherapy. Ten patients died from disease recurrence and subsequent chemoresistance. Conclusions: ASCT as a consolidation for MCL patients is found to be an effective and safe procedure.